Hábitos alimentarios y su relación en la resistencia a la insulina en adultos del Hospital General Quevedo en el periodo de octubre 2024 – mayo 2025. - Araujo Flores, Kiara Maybeth (2025)
Eating habits are defined as a set of behaviors and conducts that collectively influence the selection, preparation, and consumption of food. Insulin resistance is characterized by a decrease in the body's ability to respond adequately to insulin, the key hormone in the regulation of glucose metabolism. Objective: To determine the relationship between eating habits and insulin resistance in adults at the Quevedo General Hospital during the period October 2024 - May 2025. Methodology: This research was field, non-experimental, correlational with a cross-sectional approach. Results: The sample consisted of 132 adults, of which 57.6% were female and 42.4% male. According to age, adults aged 26 to 35 years predominated, representing 31.1%, followed by those aged 36 to 45 years with 28%, those aged 18 to 25 years with 25% and finally, adults aged 46 to 50 years, representing 15.9%. Regarding dietary habits, 54.5% of participants consumed cereals and derivatives daily, while 40.9% included vegetables in their diet, and 40.2% consumed milk and derivatives. On a weekly basis, 35.6% of adults ate legumes three or more times a week, 28.8% consumed milk and derivatives with the same frequency, and 24.2% reported a similar consumption of meat. On the other hand, it was highlighted that 37.9% of adults never consumed sweets, and 31.8% did not ingest sugar; it was evident that adults with unhealthy eating habits had a higher prevalence of insulin resistance, reaching 55.3%, while those who maintained healthy habits presented a considerably lower percentage, only 20.5%. Regarding insulin resistance, it was found that 65.2% of the sample studied presented this condition, while 34.8% did not. Finally, a significant relationship was identified between eating habits and insulin resistance with a value of (p = < .001). In conclusion, eating habits influence insulin resistance, which is why the importance of intervening with a nutritional education strategy to improve the health of the population studied is highlighted.